MODEL PEMBELAJARAN LOMPAT TINGGI GAYA FLOP PADA SISWA SEKOLAH MENENGAH PERTAMA - M. Hariadi Hidayat; Firmansyah Dlis; Iman Sulaiman (Jurnal Penjaskesrek, 2019)
The aim of this research and development is to produce the Flop Style High Jump learning model for junior high school students. This research uses research & development (R & D) research methods from Borg and Gall. The subjects in this research and development are Jakarta Junior High School students, which consist of 20 limited testing students (small group trials), 40 main trial athletes (field testing) and 50 Test effectiveness models. The stages in this study were: (1) needs analysis, (2) model development planning, (3) expert judgement, (4) limited testing (small group trials), (5) main trials (large group / field trials), (6) effectiveness testing. Effectiveness testing using the High Jump Style Flop motion assessment test to determine the level of high jump ability in the flop style of junior high school students, before and after the treatment of the flop style high jump learning model. From the preliminary tests performed, the average flop style jump learning average was 42.47, then after being given treatment in the form of a flop style high jump learning model, the flop style high jump level was 83.75. Then the flop style high jump learning model is effective in improving flop style high jump learning for junior high school students. Based on the results of the development, from the results of field trials and discussion of research results it can be concluded that: 1) With this flop style high jump learning model, students can learn and carry out learning effectively and efficiently. 2) With the flop style high jump learning model material that researchers have developed, students can understand theory material and high jump practice quickly and correctly. Abstrak Tujuan dari penelitian dan pengembangan ini adalah untuk menghasilkan model pembelajaran Lompat Tinggi Gaya Flop untuk siswa SMP. Penelitian ini menggunakan metode penelitian pengembangan Research & Development (R & D) dari Borg and Gall. Subyek dalam penelitian dan pengembangan ini adalah siswa SMP Jakarta, yang terdiri dari 20 siswa uji coba terbatas (uji coba kelompok kecil), 40 atlit uji coba utama (field testing) dan 50 Uji efektifitas model. Tahapan dalam penelitian ini adalah: (1) analisis kebutuhan, (2) perencanaan pengembangan model, (3) evaluasi ahli, (4) ujiobaterbatas (ujicoba kelompok kecil), (5) ujicobautama (ujicoba kelompok besar/lapangan), (6) ujicoba efektivitas. Ujicoba efektivitas menggunakan tespenilaian gerak Lompat Tinggi Gaya Flop untuk mengetahui tingkat kemampuan lompat tinggi gaya flop siswa SMP, sebelum dan setelah perlakuan model pembelajaran lompat tinggi gaya flop. Dari tes awal yang dilakukan diperoleh rata-rata pembelajaran lompat tinggi gaya flop sebesar 42,47, kemudian setelah diberikan perlakuan berupa model pembelajaran lompat tinggi gaya flop diperoleh tingkat lompat tinggi gaya flop sebesar 83,75. Maka model pembelajaran lompat tinggi gaya flop ini efektif dalam meningkatkan pembelajaran lompat tinggi gaya flop untuk siswa SMP. Berdasarkan hasil pengembangan, dari hasil uji coba lapangan dan pembahasan hasil penelitian dapat disimpulkan bahwa: 1) Dengan model pembelajaran lompat tinggi gaya flop ini, siswa dapat mempelajari dan melaksanakan pembelajaran secara efektif dan efisien. 2) Dengan materi model pembelajaran lompat tinggi gaya flop yang telah peneliti kembangkan, siswa dapat menguasai materi teori dan praktik lompat tinggi dengan cepat dan benar. Kata Kunci: Pengembangan, Model, Pembelajaran,Lompat Tinggi Gaya Flop